A deadly hole: postmortem multislice computed tomography of gunshot injury - Ab. Hamid, Suzana; Muhammad Noor, Muhammad Helmi; Zainun, Khairul Anuar (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
We report a case of a fatal gunshot injury to the chest which illustrates the compatibility of the Postmortem Multislice Computed Tomography (PMCT) features with that of conventional forensic autopsy findings. This case demonstrates that the PMCT has high potential to enhance the investigation and performance of conventional forensic autopsy.